Manajemen Perubahan Kepala Madrasah Sebagai Inovator Dalam Peningkatan Mutu Pendidikan Di MTS Muhammadiyah Tanjung Ampalu Kabupaten Sijunjung - Miftahul Marsena; Abhanda Amra; Rina Delfita; Marjoni Immamora; Elda Herlina (LPPM Institut Pendidikan Nusantara Global, 2026)
This study analyzes the change management practices of the madrasah principal as an innovator in improving educational quality at MTs Muhammadiyah Tanjung Ampalu, Sijunjung Regency. The study was motivated by the madrasah's initial condition as an institution facing a negative public stigma and declining community interest. A qualitative case study design was employed from July to September 2025. Data were collected through participant observation, in-depth interviews, and document analysis involving eight key informants consisting of the principal, vice principal, teachers, and madrasah committee members. Data were analyzed using the interactive model of Miles, Huberman, and Saldana through coding, categorization, theme development, data display, and conclusion drawing. Trustworthiness was ensured through source and technique triangulation. The findings reveal a change management pattern that integrates Lewin's three stages with four dimensions of educational quality: input, process, output, and outcome. At the unfreezing stage, the principal acted as a quality gatekeeper by reconstructing admission standards, strengthening teacher linearity, and prioritizing digital facilities. At the moving stage, the principal developed a hybrid innovation model that combined digital learning, tahfizh programs, literacy activities, and humanistic supervision to reduce resistance. At the refreezing stage, the change was institutionalized through social branding, in which student achievements and religious roles in the community became evidence of quality improvement. The scientific contribution of this study lies in the formulation of a contextual madrasah change management model that connects quality gatekeeping, hybrid innovation, and social branding as a strategy for restoring public trust. The study implies that madrasah principals need to manage change not only through administrative reform, but also through cultural transformation, community engagement, and sustainable quality institutionalization.